DDEL-02. Intra-arterial Delivery for Novel Combinatorial Chemotherapies in Choroid Plexus Carcinoma. (3rd June 2022) - Martin, Brice; Garman, Tyler; Laramee, Madeline; Wang, Amy; Hagen, Natalie; Dahmane, Nadia; Thomas, Craig; Souweidane, Mark
Abstract: Choroid plexus carcinoma (CPC) is a rare infantile brain tumor with an aggressive clinical course that often leaves children with debilitating side effects due to aggressive and toxic chemotherapies. New delivery routes such as intra-arterial (IA) route are being explored to limit toxicity and improve efficacy. To identify novel compounds that may be used in this context, we conducted a high-throughput screen (HTS) informing on the cytotoxicity of 2454 compounds, including some currently approved for IA in other brain tumors, that identified multiple active drugs on a human primary CPC cell line. Key molecular targets previously identified in CPC literature such as mTOR, PDGFR, ATR, CDK, FGFR1 and PI3K were enriched relative to other targets in the screen. Importantly, a combination screen with a wide variety of targets revealed multiple synergistic combinations. We examined two key combinations (topotecan/elimusertib and melphalan/elimusertib) based on mechanistic alignment and translational potential through extended in vitro validation and transcriptome analyses. Pharmacokinetic assays established increased drug brain penetrance with IA delivery when compared with intravenous delivery. Ultimately, a single intra-arterial administration of melphalan combined with systemic administration of elimusertib led to a significant increased survival in a CPC genetic mouse model. This study underscores the efficacy of IA delivery and identifies a promising therapeutic option for the treatment of CPC.